Migration and Identity in a Post-National World - Tonkiss, K.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Katherine Tonkiss offers a succinct account of constitutional patriotism theory, specifically arguing that it involves a commitment to free migration. She draws on qualitative research to explore the implications of this claim for the dynamics of post-national identity and belonging in local communities.
Keywords: Great Britain—Politics and government; Sociology; Economic development; Social policy; Emigration and immigration; Political sociology; British Politics; Sociology, general; Development Studies; Social Policy; Migration; Political Sociology